ASF1B Promotes Oncogenesis in Lung Adenocarcinoma and Other Cancer Types - Zhang, Wencheng; Gao, Zhouyong; Guan, Mingxiu; Liu, Ning; Meng, Fanjie; Wang, Guangshun (Frontiers in Oncology, 2021)
Anti-silencing function 1B histone chaperone (ASF1B) is known to be an important modulator of oncogenic processes, yet its role in lung adenocarcinoma (LUAD) remains to be defined. In this study, an integrated assessment of The Cancer Genome Atlas (TCGA) and genotype-tissue expressi on (GTEx) datasets revealed the overexpression of ASF1B in all analyzed cancer types other than LAML. Genetic, epigenetic, microsatellite instability (MSI), and tumor mutational burden (TMB) analysis showed that ASF1B was regulated by single or multiple factors. Kaplan-Meier survival curves suggested that elevated ASF1B expression was associated with better or worse survival in a cancer type-dependent manner. The CIBERSORT algorithm was used to evaluate immune microen vironment composition, and distinct correlations between ASF1B expression and immune cell infiltration were evident when comparing tumor and normal tissue samples. Gene set enrichment analysis (GSEA) indicated that ASF1B was associated with proliferation- and immunity-related pathways. Knocking down ASF1B impaired the proliferation, affected cell cycle distribution, and induced cell apoptosis in LUAD cell lines. In contrast, ASF1B overexpression had no impact on the malignant characteristics of LUAD cells. At the mechanistic level, ASF1B served as an indirect regulator of CKS1B, POLE3, and DHFR as established through proteomic profiling and IP-MS analyses. Overall, these data suggested that ASF1B serves as a tumor promoter and potential target for cancer therapy, and provided us with clues to better understand the importance of ASF1b in many types of cancer.